Review on the characteristic properties of crumb rubber concrete - Azunna, Sunday U.; Aziz, Farah N.A.A.; Rashid, Raizal S.M.; Bakar, Nabilah B.A. (Elsevier, 2024)
The global scientific research circle and government agencies face a number of serious environmental challenges, one of which is the recycling of "End of Life Tires" (ELT). An estimation of one billion tires is expected to end their useful life annually, of which only roughly 50% are recycled at the moment, with the remainder ending up in landfills. Consequently, to solve this gap in the EL T's utilization rate, it is imperative to enhance the current application and furthermore create new applications for recycled tire materials. One of such areas that is currently being investigated is the introduction of waste tire into concrete as partial replacement of natural aggregates in concrete production. Despite its great prospects, it has drawbacks such as lack of proper bonding with the cement matrix and weak rubber intrinsic strength, which make it unsuitable for widespread usage as an aggregate. To get past this obstacle, numerous rubber treatment techniques that enhance the mechanical characteristics of rubber concrete remarkably as well as the bonding properties have been studied by researchers. The impact of rubber percentage replacement, rubber aggregate size and different treatment techniques on various mechanical characteristics of rubber concrete are examined in this review paper. But in order for the concrete industry to embrace it, the researchers need to devise a rubber treatment technique that can tackle the issues of high combustible and the harmful gases that are released from the rubber aggregates when they come in contact with fire.